Comparing Criminologists’ Views on Crime and Justice Issues With Those of the General Public - Griffin, Timothy (Criminal justice policy review, 2018)
We report the results of a survey of criminology and criminal justice (CCJ) scholars asking their responses to the same questions posed annually to the general public in Gallup public opinion polls. We found CCJ scholars to be more likely to hold more liberal positions on these issues than the general public. The findings indicate a disconnect between popular crime and justice perspectives (and resultant crime policy formation) and the “experts” presumably best trained and informed on how to go about crime policy. We argue for a renewed discussion among CCJ scholars regarding the relevance and role of academic expertise in crime policy formation and offer suggestions for how CCJ scholars might “go public” in influencing policy decisions.